PERAN PENYULUH AGAMA DALAM MELAKSANAKAN LAYANAN BIMBINGAN KONSELING ISLAM TERHADAP CALON JEMAAH HAJI KOTA BANDUNG - rohaeti, eti; Lilis Satriah; Dudy Imanuddin Effendi (UIN Sunan Kalijaga Yogyakarta, 2024)
This research will examine problems in organizing the 2023 Hajj, such as health anxiety, lack of companions, as well as other psychological problems that have the potential to affect Hajj pilgrims. This research hopes to understand the efforts made by Islamic religious instructors with their duties and functions as educational, task and effort. consultative function, duties and functions as an advocate function and consultative efforts and functions. This research uses a descriptive qualitative approach regarding data collection techniques related to observation, interviews, literature studies and documentation. Data processing is related to data reduction, presenting data, analyzing and drawing conclusions. The results of your research show that there are significant efforts made by religious instructors in carrying out their various functions for prospective Hajj pilgrims. Details of the research results include: 1) Informative Function: Religious instructors play a role in providing clear and complete information regarding various aspects related to the Hajj pilgrimage, including departure procedures, travel, accommodation in the holy land, as well as the importance of vaccination and maintaining health during the pilgrimage. 2) Educational Function: Religious instructors provide education to prospective Hajj pilgrims through practice, training and instilling the spiritual values ​​of the Hajj pilgrimage. They also provide guidebooks, video tutorials and other educational materials to help the congregation understand. 3). Consultative Function: Religious instructors provide consultation services to help prospective pilgrims resolve various problems they face, both before and during worship. 4). Advocative: Accompanying elderly pilgrims and ensuring their rights are protected. Keywords: role of religious instructors, Islamic counseling guidance, prospective Hajj pilgrims.